The Role of Human Resource Management in Increasing the Professionalism of Islamic Teachers at MTs Al-Hamidy Kebon Talo - Padilah, Noviatun; Thohri, Muhammad; Badrun, Badrun (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This research aims to describe the role of human resource management in increasing the professionalism of Islamic teachers at MTs Al-Hamidy Kebon Talo. This research uses descriptive qualitative methods. Data collection techniques were carried out using interviews, observation and documentation. The resource persons in this research were the principal, Vice Principal for Curriculum, and MTs Al-Hamidy teachers. Data was analyzed by data reduction, data presentation and verification. The results of the research can be concluded, including: human resource management has an important role In developing the professionalism of Islamic teachers, this can be seen through the human resource management process in developing the professionalism of Islamic teachers at MTs Al-Hamidy, namely 1) Planned HR Planning: HR planning at MTs Al-Hamidy involves analyzing the school's needs and staff development goals, so that training and development programs can be prepared appropriately. 2) Strict Recruitment and Selection: Strict policies in the teacher recruitment and selection process ensure that the teachers recruited have the appropriate qualifications and competencies, and are able to instill Islamic values in students in a professional manner. 3) Continuous Competency Development: HR management is active in identifying teacher professional development needs and providing support in training and the use of technology to improve teacher capabilities, especially in the IT field. 4) Attention to Well-Being and Motivation: Attention to teacher welfare as well as providing incentives and motivation helps in improving teacher performance and ability in facing challenges in the era of digital education. 5) Building an Organizational Culture that Encourages Professional Growth: An organizational culture that encourages collaboration between teachers and creates a positive work environment helps in motivating teachers to improve their professionalism.